Transmission of Carbapenemase-Producing Hypervirulent Klebsiella pneumoniae in Georgia, 2018–2019. (October 2020) - Negley, Jeanne; Smith, Elizabeth; Walters, Maroya; Parrott, Tonia; Stanton, Richard; Ham, David; Kara, Jacobs Slifka; Kopp, Patricia; Connelly, Mary; Tiga, Gebre; McAllister, Gillian; Halpin, Alison; et al.
Abstract : Background: In April 2019, the Georgia Department of Public Health (DPH) initiated whole-genome sequencing (WGS) on NDM-producing Enterobacteriaceae identified since January 2018. The WGS data analyzed at CDC identified related Klebsiella pneumoniae isolates with hypervirulence markers from 2 patients. Carbapenemase-producing hypervirulent K. pneumoniae (CP-hvKP) are rarely reported in the United States, but they can to cause serious, highly resistant, invasive infections. We conducted an investigation to identify cases and prevent spread. Methods: We defined a case as NDM-producing K. pneumoniae with ≥4 hypervirulence markers identified by WGS, isolated from any specimen source from a Georgia patient. We reviewed the case patient's medical history to identify potentially affected facilities. We also performed PCR-based colonization screening and retrospective and prospective laboratory-based surveillance. Finally, we assessed facility infection control practices. Results: Overall, 7 cases from 3 case patients (A, B, and C) were identified (Fig. 1). The index case specimen was collected from case-patient A at ventilator-capable skilled nursing facility 1 (vSNF1) in May 2018. Case-patient A had been hospitalized for 1 month in India before transfer to the United States. Case-patient B's initial isolate was collected in January 2019 on admission to vSNF2 from a critical access hospital (CAH). The CAH laboratory retrospectively identified case-patient C, who overlapped with case-patient B at the CAH in October 2018. The CAH and the vSNF2 are geographically distant from vSNF1. Case-patients B and C had no known epidemiologic links to case-patient A. Colonization screening occurred at vSNF1 in May 2018, following detection of NDM-producing K. pneumoniae from case-patient A ∼1 year before determining that the isolate carried hypervirulence markers. Among 30 residents screened, 1 had NDM and several had other carbapenemases. Subsequent screening did not identify additional NDM. Colonization screening of 112 vSNF2 residents and 13 CAH patients in 2019 did not reveal additional case patients; case-patient B resided at vSNF2 at the time of screening and remained colonized. At all 3 facilities, the DPH assessed infection control practices, issued recommendations to resolve lapses, and monitored implementation. The DPH sequenced all 27 Georgia NDM– K. pneumoniae isolates identified since January 2018; all were different multilocus sequence types from the CP-hvKP isolates, and none possessed hypervirulence markers. Conclusions: We hypothesize that CP-hvKP was imported by a patient hospitalized in India and spread to 3 Georgia facilities in 2 distinct geographic regions through indirect patient transfers. Although a response to contain NDM at vSNF1 in 2018 likely limited CP-hvKP transmission, WGS identified hvKP and established the relatedness of isolates from distinct regions, thereby directing the DPH's additional containment activities to halt transmission. Funding: None Disclosures: None